Mechanical Properties and Accuracy of Additively Manufactured Silicone Soft Tissue Materials - Pei Xin Chen; John M. Aarts; Joanne Jung Eun Choi (Journal of Manufacturing and Materials Processing)
The objective of this study was to measure and compare the mechanical properties of conventional and three additively manufactured soft tissue silicone materials, while evaluating the precision of additively manufactured (AMed) materials through different printing angles. Three additively manufactured soft tissue silicone materials were used, in addition to one conventional self-curing injectable silicone material as a control. AMed materials were divided into three groups with three build angles. Mechanical testing was conducted for tensile and compressive strength by a universal testing machine and Shore A hardness by a durometer. Accuracy analysis of additively manufactured materials (n = 20/group) was performed following superimposition and root mean square (RMS) calculation. Statistical differences between the groups were assessed with a one-way analysis of variance (ANOVA) and Tukey’s post hoc test at a significance level of p < 0.05. Scanning Electron Microscopy (SEM) analysis was performed for fracture surface analyses. The tensile strength of all additively manufactured silicone soft tissue materials was significantly lower (p < 0.0001) than that of the control material. All additively manufactured soft tissue material groups had significantly higher compressive strengths (p < 0.0001) and Shore A hardness values. Accuracy analysis showed no significant difference between the groups when compared at the same printing angle (0°, 45°, and 90°); however, within each material group, printing at 45° had higher RMS values than specimens printed at an angle of 0° and 90°. The conventional soft tissue material (control) had a significantly higher tensile strength than all the AMed soft tissue materials, whereas the opposite trend was found for flexural strength and shore hardness. When selecting an AMed material for soft tissue casts used during implant restoration fabrication, it is recommended to print the soft tissues at either 0° or 90°.